2010
DOI: 10.4061/2010/151097
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of the CNS Innate Immune Response Is Vital for the Restoration of Tissue Homeostasis (Repair) after Acute Brain Injury: A Brief Review

Abstract: Neurons and glia respond to acute injury by participating in the CNS innate immune response. This involves the recognition and clearance of “not self ” pathogens and “altered self ” apoptotic cells. Phagocytic receptors (CD14, CD36, TLR–4) clear “not self” pathogens; neurons and glia express “death signals” to initiate apoptosis in T cells.The complement opsonins C1q, C3, and iC3b facilitate the clearance of apoptotic cells by interacting with CR3 and CR4 receptors. Apoptotic cells are also cleared by the scav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 190 publications
(341 reference statements)
0
42
0
Order By: Relevance
“…Previous in silico analyses suggested that inflammatory response markers are able to differentiate patients with SZ or BD (Griffiths et al, 2010;Ricklin et al, 2010). A systematic meta-analysis of 13 studies reviewed evidence of peripheral cytokine alterations in BD and found differences between patients and controls and between phases of disease within patients (Munkholm et al, 2013), suggesting that different symptoms are related to activation of different processes within the cell.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous in silico analyses suggested that inflammatory response markers are able to differentiate patients with SZ or BD (Griffiths et al, 2010;Ricklin et al, 2010). A systematic meta-analysis of 13 studies reviewed evidence of peripheral cytokine alterations in BD and found differences between patients and controls and between phases of disease within patients (Munkholm et al, 2013), suggesting that different symptoms are related to activation of different processes within the cell.…”
Section: Discussionmentioning
confidence: 98%
“…Another protein expressed in microglial cells is AIF1, a marker of activated macrophages (Fukui et al, 2012). SERPIN1 has an important role as a self-defense protein that modulates the activation of microglia (Griffiths et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrocytes are also capable of inducing T-cell apoptosis and may thereby control the spread of peripheral lymphocyte-mediated inflammation following severe TBI. For example, following TBI, reactive astrocytes upregulate CD95 and CD95R to induce lymphocyte apoptosis through a CD95/CD95R-dependent mechanism, though astrocytes themselves remain protected (Bechmann et al, 2000; Bechmann et al, 2002; Griffiths et al, 2010). …”
Section: Scar-forming Reactive Astrocytes Form Functional Barriers Armentioning
confidence: 99%
“…The Wld s mouse, which displays a delayed Wallerian degeneration phenotype similar to SARM −/− mice, is also deficient in cytokine production suggesting that the processes are intricately linked (12). In addition to promoting repair of damaged brain tissue, glial activation and cytokine production in the CNS may injure bystander cells (13, 14). In other organs, this collateral damage is typically reversible, owing to the regenerative capacity of the tissue, but repopulation of cells is limited in the CNS (15).…”
Section: Introductionmentioning
confidence: 99%